The Pathway of Green Shift Research: Insight From Bibliometric Study on Sustainable Competence and Organizational Green Culture - Gusti Meinar Girda Ariani; Nurul Hasanah; Farida Yulianti; Syahrani Syahrani; Siti Mujanah (Business Management, 2025)
This study aims to map the development of scientific literature on sustainable competence and green organizational culture as two fundamental pillars in shaping pro-environmental behavior within organizations. Using a bibliometric approach, the study analyzes 177 scientific articles published between 2015 and 2025, sourced from Scopus and Google Scholar databases. The analysis was conducted with the aid of VOSviewer software, generating network, overlay, and density visualizations to illustrate the conceptual interconnections among key themes. The findings reveal that while sustainability, green innovation, and green human resource management dominate the discourse, the integration between individual competence and organizational culture as drivers of ecological behavior has yet to become a central focus in academic studies. The visualizations indicate that keywords such as “sustainable competence” and “green organizational culture” remain peripheral in mainstream discussions. This suggests a significant research gap in bridging macro-structural and micro-behavioral approaches within the green organization context. The study contributes theoretically by offering an integrative approach to understanding human-centered sustainability dynamics and practically by guiding the development of organizational strategies that prioritize competency building and collective values. The implications underscore the need for strategic interventions in human resource training, cultural transformation, and policy formulation that embed sustainability as a core organizational element. Thus, this article expands the intellectual horizon of sustainability management and opens new pathways for future interdisciplinary research.